Identifying spatiotemporal variations in groundwater-surface water interactions using shallow pore water chemistry in the lower Jordan river. (September 2019) - Hillel, Noa; Wine, Michael L.; Laronne, Jonathan B.; Licha, Tobias; Be'eri-Shlevin, Yaron; Siebert, Christian
Highlights: Porewater from shallow sediment cores from the trans-boundary lower Jordan river were chemically analyzed. Sub-riverine groundwater upwelling that was previously thought to be generally steady is found to vary spatiotemporally. Upwelling is seasonally dependent and forced by winter flux, though expressed differently in space and time. Given this information groundwater intrusion estimations may be revised especially when they are highly saline or polluted. Abstract: Groundwater-surface water interactions as result of in- and effluent conditions along a stream may have a strong impact on the quantity and quality of the river water. These interactions are controlled by river morphology and by transient hydraulic gradients between river and surrounding groundwater. Here we document the existence of spatiotemporal variations in groundwater-surface water interactions in the bed of the Lower Jordan River through pore water analysis of shallow sediment cores using major ions (Na +, Mg 2+, Ca 2+, Cl −, Br −, SO4 2− ) and stable isotopes (δ 18 O, δ 2 H). Our results demonstrate that temporal variations are neither spatially uniform nor steady. Upwelling of groundwater is seasonally dependent and forced by a winter pulse of groundwater recharge and by estival low river discharge.